Metodologi Tafsir al-Munir Karya AGH Daud Ismail - Hasani Ahmad Said; Muh. Akbar Nasrulah; Desvia Nur Syafitri; Alif Ardianto (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2024)
One of the interpretations of the Qur’an using the local language is Tafsir al-Munir by AGH. Daud Ismail who is a great scholar from the land of Bugis who first interpreted the Qur'an as a whole. He presents a Buginese Interpretation so that the divine messages contained in the Qur'an can be understood by the wider community, especially the Bugis community. This research is a qualitative research that is descriptive in nature, at least provides an overview regarding AGH. Daud Ismail and the characteristics of his interpretation and the application of his interpretation with the Tahlili method. The approach used in this research is linguistics, interpretation science approach, and social approach. Tafsir al-Munir Mabbasa Ugi written by AGH. Daud Ismail followed the mushafi pattern, he wrote it in 10 volumes, each volume consisting of 3 chapters. The systematics of writing by writing the verses of the Qur'an side by side with the translation, the verses of the Qur'an are written on the right and the Bugis language translation on the left, mentioning the order of the surahs and verses at the beginning of the discussion, in each interpretation one verse, two verses, or several verses of the Qur'an arranged in such a way as to provide a unified meaning, or these verses are considered one group. Interpretation of the Qur'an using the tahlili method is an attempt to explain the Qur'an by describing its various aspects and explaining what is meant by the Qur'an.